2017
DOI: 10.1128/aac.02296-16
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Is Selectively Killed by Rifampin and Rifapentine in Hypoxia at Neutral pH

Abstract: The activities of rifampin, rifapentine, bedaquiline, PA-824, clofazimine, nitazoxanide, isoniazid, amikacin, moxifloxacin, niclosamide, thioridazine, and pyrazinamide were tested against nonreplicating (dormant) Mycobacterium tuberculosis H37Rv under conditions of hypoxia at pHs 5.8 and 7.3, mimicking environments of cellular granulomas and caseous granulomas, respectively. At pH 5.8, several drugs killed dormant bacilli, with the best being rifampin and rifapentine. At pH 7.3, only rifampin and rifapentine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…skin or intestinal tuberculosis infections [57] . Subsequently, a number of research groups have reported the ability of niclosamide and related salicylanilide derivatives to inhibit the growth of M. tuberculosis and reported the effect of pH on growth inhibition [58] , [59] , [60] .…”
Section: Niclosamide and Bacteriamentioning
confidence: 99%
“…skin or intestinal tuberculosis infections [57] . Subsequently, a number of research groups have reported the ability of niclosamide and related salicylanilide derivatives to inhibit the growth of M. tuberculosis and reported the effect of pH on growth inhibition [58] , [59] , [60] .…”
Section: Niclosamide and Bacteriamentioning
confidence: 99%
“…Briefly, for preparation of NR, hypoxic (H) cells, M. tuberculosis H37Rv log-phase cultures were diluted in Dubos-Tween-albumin broth (DTAB) adjusted to pH 7.3 (10,11) and incubated at 37°C for 12 days (H12) in 20-by 125-mm stirred tubes (120 rpm) containing 16 ml of culture (0.5 headspace ratio) (9) with the caps tightly screwed and tight rubber caps put under the screw caps. Control tubes with 1.5 g/ml of methylene blue as an indicator of oxygen depletion were also incubated.…”
mentioning
confidence: 99%
“…Noticeable decolorization of methylene blue was observed around day 12. Drugs were added by syringe to H12 cultures at their maximum concentration of drug in serum (C max ) (g/ml) (10,12,13) as follows: R, 8; I, 2; E, 4; PA-824 (PA), 2; nitazoxanide (NZ), 10; sutezolid (SZ), 1. Pyrazinamide was used at 100 g/ml.…”
mentioning
confidence: 99%
“…NRP-2 cells developed a thickened outer layer that helped in restricting RIF entry [85]. Our group used the Wayne model at different pHs: pH 6.6, the pH or culture media [86], pH 5.8, to mimic the environment of cellular granulomas [87], pH 7.3, to mimic the environment of caseous granulomas [88]. We found that at pH 5.8, several drugs killed NR bacilli, with the best being the rifamycins RIF and rifapentine (RFP), while at pH 7.3, only RIF and RFP killed dormant bacilli out of 12 drugs tested [88].…”
Section: Phenotypic Drug-resistance Of Mtbmentioning
confidence: 99%
“…Our group used the Wayne model at different pHs: pH 6.6, the pH or culture media [86], pH 5.8, to mimic the environment of cellular granulomas [87], pH 7.3, to mimic the environment of caseous granulomas [88]. We found that at pH 5.8, several drugs killed NR bacilli, with the best being the rifamycins RIF and rifapentine (RFP), while at pH 7.3, only RIF and RFP killed dormant bacilli out of 12 drugs tested [88]. Since the rifamycins were the only agents sterilizing caseum obtained from rabbits [35,36], our model could mimic caseum to measure drug activity against NR Mtb in this environment.…”
Section: Phenotypic Drug-resistance Of Mtbmentioning
confidence: 99%